THE SINO-KOREAN CRATON AND SUPERCONTINENT HISTORY: PROBLEMS AND PERSPECTIVES - Rogers J.J.W.; Santosh M. (My University, 2006)
The Sino-Korean Craton (SKC) is an enigmatic block in the history of supercontinents older than Pangea. Its accretion to Eurasia and the effect of the broad region of Mesozoic-Cenozoic extension in northern Eurasia that crosses the eastern part of the SKC are among several problems that need to be resolved in understanding the configuration of SKC and the overprinting of earlier histories in this block. We present a synopsis of these problems and perspectives for future research. © 2006 Published by Elsevier B.V. on behalf of International Association for Gondwana Research.
Keywords: ACCRETION; CONFIGURATION; EXTENSION; SINO-KOREAN CRATON; SUPERCONTINENTS